PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP MOTIVASI MAHASISWA KEPERAWATAN - YOSI OKTARINA; NURHUSNA NURHUSNA; DINI RUDINI (Jurnal Ners, 2022)
Motivation is very important for every student. Student motivation tends to fluctuate. Project based learning (PjBL) is a learning method that can encourage creativity, critical thinking skills, and student independence. The purpose of this study was to determine the effect of PjBL on student motivation. This research is a quantitative study with a quasi-experimental design with a pre-test post-test approach with a control group. The sampling technique was total sampling with a total sample of 84 people who were divided into control groups and intervention groups. In the intervention group, intervention was given through the application of the PjBL method. The measuring instrument used a questionnaire to determine the characteristics of respondents and student motivation. Data analysis used the Mann Whitney test to assess the difference in mean motivation in the control and intervention groups. The results showed that there was a difference in the mean motivation in the control group and the intervention group after giving the PjBL method of intervention (p-value < 0.001). PjBL is effective in increasing student motivation. Keywords: learning method, motivation, project based learning